The use of spanish language in the teachinglearning process of the english language with the students of the bachillerato level at “unidad educativa anexa a la Universidad Nacional de Loja”, academic year 2012 – 2013 - Ruiz Quizhpe, Paola Lorena (2014)
The present research work entitled: THE USE OF SPANISH IN THE TEACHING - LEARNING PROCESS OF THE ENGLISH LANGUAGE WITH THE STUDENTS OF THE BACHILLERATO LEVEL AT UNIDAD EDUCATIVA ANEXA A LA UNIVERSIDAD NACIONAL DE LOJA, ACADEMIC YEAR 2012-2013, had as its general objective to determine the influence of the use of Spanish in the teaching learning process of the English language, with a population of 134 students and 5 teachers. These methods were used: scientific, inductive – deductive, statistical, descriptive, synthetic and analytical. The main hypothesis stated that the use of Spanish affects the teaching learning process of the English language. The specific hypotheses were accepted according to the obtained results. The surveys applied to the teachers and students showed that the teachers are using the mother tongue during the teaching - learning process causing learning difficulties and demotivation in the learning of the English language to the students at this educational establishment.